Groundwater conservation and food security: Navigating pathways to sustainable agriculture - Singh, Vartika; Ringler, Claudia (International Food Policy Research Institute, 2024)
Most of the Earth’s liquid fresh water resources are stored as groundwater. Accessible groundwater resources are increasingly extracted for use in irrigated agriculture, industrial and domestic purposes—and constitute the globe’s most extracted natural resource. Irrigation accounts for the lion’s share of groundwater use, and groundwater contributes around a third to 40% of total consumptive irrigation use. Irrigation, in turn, contributes 40% of global food production on just under one third of the world’s harvested area. Not surprisingly, groundwater management and food security are deeply interlinked.